Application of Arbuscular Mycorrhizal Fungi (AMF) to Enhance Biomass of Uncaria gambir (Gambier) in Ex Coal Mining Soil - Hervani, Dini; Febjislami, Shalati; Armansyah, Armansyah; Kusumawati, Aries; Lopita, Septy; Rahmad, Rahmad (Journal of Tropical Crop Science, 2025)
Gambier cultivation faces limitations due to decreasing land availability; however, utilizing ex-coal mining land presents a promising alternative for sustainable expansion. Ex-coal mining land has the problem of low available nutrients because of bonded nutrients. Arbuscular Mycorrhiza Fungi (AMF) can help release bound nutrients into available nutrients, so that on ex-coal mining land, there is an increase in the amount of available nutrients that can be absorbed by plants for their growth. The study aimed to determine the effect of different types of arbuscular mycorrhizal fungi (AMF) and their doses on the biomass of gambier seedlings planted in ex-coal mining soil. An experimental design was employed using a randomized block design with two treatments: the types of arbuscular mycorrhizal fungi (AMF) (Acaulospora sp., Glomus sp., and Gigaspora sp.) and the AMF dosages (0, 5, 10, 15, and 20 g per seedling). All treatments were replicated three times. The parameters observed were soil chemical analysis, root colonization by arbuscular mycorrhizal fungi (AMF), shoot and root fresh and dry weights, net assimilation rate, and relative growth rate. The results obtained showed that AMF type and dose treatment had a significant effect on all parameters, except for the relative growth rate, and there was no interaction between the two treatments. Glomus sp. at a dose of 20 g per seedling provided the best influence in increasing gambier seedlings' biomass under the ex-coal mine soil.